Can we test for supplier-induced demand by comparing informed with uninformed consumers? - Calcott, Paul (School of Management Working Papers, 1995)
Two tests for supplier induced demand are evaluated. Both tests are based on the greater vulnerability to demand inducement of less informed consumers. The first test is whether less informed consumers have higher utilisation of a procedure than more informed consumers. The second is whether they have higher utilisation, given that they have sought medical advice. Both tests are shown to be flawed. The absence of demand inducement is compatible with positive results of either test and the presence of demand inducement is compatible with negative results of both tests.